Cultural intermediaries connecting communities : revisiting approaches to cultural engagement / edited by Phil Jones, Beth Perry and Paul Long. - Jones, Phil; Perry, Beth; Long, Paul (Connected communities (Bristol, England), 2019)
This book considers the importance of cultural intermediaries, analysing their role as mitigators of the worst effects of social exclusion and examining the necessity to engage communities with different forms of cultural consumption and production.